Implementation of Singing Methode Arabic Vocabulary Mastery in Early Childhood - Dian Risky Amalia; Vina Anggraini; Adrian Rodgers (Journal of Childhood Development, 2022)
Improving the quality of learning Arabic is still considered difficult by students. One thing that can be done is to find effective methods for teaching Arabic so that students can more easily understand and understand it. The use of the singing method is so that students who are afraid, lazy and don't like Arabic become interested and happy in participating in learning. The research instrument used by the researcher was interviews, observations, and data collection. The percentage results that can be taken from mastery of Arabic vocabulary are as follows 15.8% for the BB stage, which is not yet developed, 36.8% for the MB stage, which is starting to create, 42% for the SB stage, which is already developed, and 5.26% for the BSH stage, namely developing according to expectations. Suggestions for researchers to innovate more in methods of learning Arabic.